Learning about acute care via simulators - Mat Nor, Mohd Basri (University of Malaya Press, 2009)
Simulation base learning or simulation base training is a new paradigm in medical education. The traditional training from exposure to the actual acute care patients can be time consuming and unnecessarily prolongs the learning curve. It is also limited by unpredictable occurence of emergencies and ethical consideration regarding the advisability of allowing junior medical doctors or nursing staff to manage acutely il patiens. Patient simulation provides a safe learning environment in order to improve the skills of the average care provider and to enhance the quality of patient care. The learning method is experiential in the setting of virtual reality and simulation training equipment.